2012
DOI: 10.3390/s120607598
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Air Flow Generated by an Air-Assisted Sprayer Equipped with Two Axial Fans Using a 3D Sonic Anemometer

Abstract: The flow of air generated by a new design of air assisted sprayer equipped with two axial fans of reversed rotation was analyzed. For this goal, a 3D sonic anemometer has been used (accuracy: 1.5%; measurement range: 0 to 45 m/s). The study was divided into a static test and a dynamic test. During the static test, the air velocity in the working vicinity of the sprayer was measured considering the following machine configurations: (1) one activated fan regulated at three air flows (machine working as a traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 13 publications
4
24
0
Order By: Relevance
“…The majority of orchard sprayers in New Zealand are towbehind varieties with an anti-clockwise rotation causing the air to be lifted on the right side of the sprayer and dumped on the left. This approach leads to droplet interaction and inconsistences in the vertical profile (Manktelow & May 2011;García-Ramos et al 2012). For example, Khot et al (2012a) observed that flux profiles at distances of 3.0 to 4.5 m on the right side of the sprayer (with nozzles and air flow at 100% open) were 49% higher than on the left side.…”
Section: Droplet Size and Velocitymentioning
confidence: 99%
“…The majority of orchard sprayers in New Zealand are towbehind varieties with an anti-clockwise rotation causing the air to be lifted on the right side of the sprayer and dumped on the left. This approach leads to droplet interaction and inconsistences in the vertical profile (Manktelow & May 2011;García-Ramos et al 2012). For example, Khot et al (2012a) observed that flux profiles at distances of 3.0 to 4.5 m on the right side of the sprayer (with nozzles and air flow at 100% open) were 49% higher than on the left side.…”
Section: Droplet Size and Velocitymentioning
confidence: 99%
“…The distribution of the spray in the vicinity of the sprayer is often estimated by measuring the air flow generated by the fans. In this sense, the air flow generated by the sprayer can be characterized using high-precision anemometers such as sonic anemometers (two-dimensional or three-dimensional) which are used to measure the velocity components for different heights, sections, and distances from the sprayer [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…This four-transducer orthogonal design, proposed in [4], is recognized as 2D ultrasonic anemometer. A 3D ultrasonic anemometer in [5] provides less aerodynamic turbulence by having complex design and mathematical equations. However, the design and implementation of ultrasonic anemometer mentioned is still very expensive.…”
Section: Introductionmentioning
confidence: 99%